Alterações fitotécnicas em genótipos de cafeeiro Conilon em resposta ao sombreamento - Torres, Cassio Fernandes (2020)
The coffee tree can be grown in different environments due to its phenotypic plasticity, as well as the existence of pre-selected genotypes. The benefits provided by shading, associated with morphological, physiological and nutritional modulations can be an important strategy for the cultivation of coffee, especially in regions where water restriction is more pronounced, high levels of solar radiation, elevated atmospheric temperature and high demand nitrogen fertilization. The objective of this work was to evaluate and quantify the morphophysiological responses of Coffea canephora genotypes to shaded and full sun cultivation. The treatments were added to the completely randomized design, in a 14x2 factorial scheme, with 14 genotypes of Coffea canephora, 2 levels of irradiance, full sun and 30% shaded. Each treatment consisted of 4 experimental units. The level of 30% shading determined based on work is already done. The 14 genotypes used are elite genotypes from the active germplasm bank of Coffea canephora of the Capixaba Institute for Research, Technical Assistance and Rural Extension. The experiment was conducted at the Experimental Farm of Bananal do Norte, belonging to Incaper, located in the municipality of Cachoeiro de Itapemirim-ES. The effect of cultivation in full sun and shade was evaluated through variables in the pellet phase: chlorophyll, flavonoid, anthocyanin indices, nitrogen balance index, leaf nitrogen content and leaf nitrogen accumulation, and at harvest: branch diameter plagiotropic, length of the plagiotropic branch, number of leaves per plagiotropic branch, unit leaf area, total leaf area, leaf dry matter per branch, number of rosettes per plagiotropic branch and plagiotropic branch harvest index. Studying the chlorophyll index, genotypes 103, 2B / 88, 108, 820/87, 207, 302, 303 and 304 stood out in full sun and genotypes 2B / 88, 80S, 820/87, 207 when shaded. Regarding the flavonoid index, genotype 104 stood out in full sun, with lower flavonoid values and genotypes 103, 2B / 88, 105, 108, 80S, 109, 820/87, 207 and 302 lower values when shaded. As for the anthocyanin index, genotypes 105, 108, 820/87, 207, 302 and 304 were the ones that showed lower values for anthocyanins in full sun, and genotypes 2B / 88, 108, 604/97, 820/87, 207, 302 and 303 had the lowest values when shaded. Analyzing the nitrogen balance index, genotypes 104 and 207 stood out in full sunlight and genotypes 2B / 88 and 207 when shaded. For leaf nitrogen content there was no significant difference between genotypes in full sun, only the level of shaded comparison showed difference, with genotypes 103, 2B / 88, 106, 104, 108, 109, 820/87, 303 and 304 those that stood out with the highest levels of leaf nitrogen. For leaf nitrogen accumulation, genotypes 108, 80S and 303 were the ones that stood out in full sun and genotypes 103, 2B / 88, 109 and 304 when shaded. Genotypes 104, 108, 207 and 303 in full sun showed higher values for the diameter of the plagiotropic branch, when shading genotypes 103, 604/97 and 207. For the length of the plagiotropic branch in full sun, genotypes 104, 108, 820 / 87, 207 and 203 stood out, already in the shaded system the genotypes 103, 2B / 88, 105, 108, 80S, 109, 604/97, 207, 302 and 303. For the number of leaves per plagiotropic branch, genotypes 108 and 303 were the ones that stood out in full sun and shaded genotypes 2B / 88, 105, 604/97 and 304. For the unit leaf area, genotypes 108, 207 and 302 stood out in full sun and genotypes 108, 820 / 87 and 207 when shaded. Analyzing the total leaf area, genotype 108 stood out in full sun and genotypes 820/87, 207, 303 and 304 when shaded. For the leaf dry matter variable, genotypes 108, 80S and 303 stood out in full sunlight and genotypes 103 and 304 when shaded. For number of rosettes, genotypes 103, 106, 104, 108, 80S, 207 and 303 stood out in full sun and genotypes 80S and 820/87 when shaded. Analyzing the harvest index, genotype 604/97 stood out in full sunlight and genotypes 106, 105 and 604/97 when shaded. In view of the above, it is possible to identify that genotypes 105, 106 (12 and 6 Vitória Incaper 8142), 80S, 820/87, 604/97, 207, 303 (408 Marilândia) and 304 have answers that may be related to greater fitness for shaded cultivation. Genotypes 104, 108, 207 and 303 showed full sun responses, reinforcing their potential for this cultivation system.